A functional substitution in the L‐aromatic amino acid decarboxylase enzyme worsens somatic symptoms via a serotonergic pathway. Issue 2 (8th June 2019) - Khoury, Samar; Piltonen, Marjo H.; Ton, Anh‐Tien; Cole, Tiffany; Samoshkin, Alexander; Smith, Shad B.; Belfer, Inna; Slade, Gary D.; Fillingim, Roger B.; Greenspan, Joel D.; Ohrbach, Richard; Maixner, William; et al.
Abstract : Objective: Heightened somatic symptoms are reported by a wide range of patients with chronic pain and have been associated with emotional distress and physical dysfunction. Despite their clinical significance, molecular mechanisms leading to their manifestation are not understood. Methods: We used an association study design based on a curated list of 3, 295 single nucleotide polymorphisms mapped to 358 genes to test somatic symptoms reporting using the Pennebaker Inventory of Limbic Languidness questionnaire from a case–control cohort of orofacial pain (n = 1, 607). A replication meta‐analysis of 3 independent cohorts (n = 3, 189) was followed by functional validation, including in silico molecular dynamics, in vitro enzyme assays, and measures of serotonin (5‐HT) plasma concentration. Results: An association with the T allele of rs11575542 coding for an arginine to glutamine substitution in the L‐aromatic amino acid decarboxylase (AADC) enzyme was replicated in a meta‐analysis of 3 independent cohorts. In a combined meta‐analysis of all cohorts, this association reached p = 6.43 × 10 −8 . In silico studies demonstrated that this substitution dramatically reduces the conformational dynamics of AADC, potentially lowering its binding capacity to a cofactor. in vitro enzymatic assays showed that this substitution reduces the maximum kinetic velocity of AADC, hence lowering 5‐HT levels. Finally, plasma samples from 90 subjects showed correlation between low 5‐HT levels and heightened somatic symptoms. Interpretation: Using functional genomics approaches, we identified a polymorphism in the AADC enzyme that contributes to somatic symptoms through reduced levels of 5‐HT. Our findings suggest a molecular mechanism underlying the pathophysiology of somatic symptoms and opens up new treatment options targeting the serotonergic system. ANN NEUROL 2019;86:168–180